Combinatorial Productivity of Spanish Verbal Periphrases as an Indicator of Their Degree of Grammaticalization - Mar Garachana; María Sol Sansiñena (Languages, 2023)
Studies on the constitution of the Spanish periphrastic system show that there is a great ease with which verbal periphrases admit different lexical items in the second verb slot as they go through their grammaticalization process. However, it has not been sufficiently explored whether the evolution of combinatorial patterns in near-synonymous periphrases follows similar grammaticalization paths. Adopting a constructionist, usage-based approach, we investigate the evolution of the so-called near-synonymous periphrases dejar de + inf and parar de + inf, as in Deja de/Para de gritar, ‘Stop shouting.’ More specifically, we discuss the semantic areas they cover, the functional distribution between the two throughout time, their evolution in terms of collostructional patterns, and their realized and potential productivity, paying special attention to the Aktionsart of the predicates in the Vinf slot. All tokens in the corpus were extracted from CORDE and analyzed in terms of morphosyntactic and semantic-pragmatic parameters, as well as contextual elements. We conduct a distinctive collexeme analysis to investigate which lexemes are strongly attracted or repelled by the Vinf slot in each construction. This analysis shows that the evolution of parar de + inf is not parallel to that of dejar de + inf and that there is a clear distribution of labor between the two constructions.